A Descent Four-term Of Liu And Storey Conjugate Gradient Method For Large Scale Unconstrained Optimization Problems - Shahrina Ismail; Ahmad Alhawarat; Ibtisam A. Masmali; Hanan Alolaiyan; Zabidin Salleh (New York Business Global, 2024)
Indexed by ERA